2020
DOI: 10.1590/s1980-6574202000030034
|View full text |Cite
|
Sign up to set email alerts
|

The relative peak power output of amateur mountain bikers is inversely correlated with body fat but not with fat-free mass

Abstract: To evaluate whether body mass (BM) and body composition may influence mountain bike cycling performance. Methods: Forty male amateur mountain bikers attended the laboratory on two non-consecutive days. At the first visit, anthropometric measures (height, BM, body fat [BF], fat-free mass [FFM] and body mass index [BMI]) and familiarization to incremental cycling test were performed. On the second visit, cyclists performed again the incremental cycling test to measure peak power output (PPO), peak power output r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Similar results were noted by other authors in various disciplines [28,29]. Arriel et al [30] showed that body mass and body composition could be determinant for mountain biking performance, where body fat negatively influenced the performance of amateur mountain bikers, but the fat-free mass did not. In sprint runners, a lower body fat is correlated with better speed performance [31].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were noted by other authors in various disciplines [28,29]. Arriel et al [30] showed that body mass and body composition could be determinant for mountain biking performance, where body fat negatively influenced the performance of amateur mountain bikers, but the fat-free mass did not. In sprint runners, a lower body fat is correlated with better speed performance [31].…”
Section: Discussionsupporting
confidence: 89%
“…However, when these performance measures are normalized to BM, the correlation coefficient is higher, suggesting that BM is an important factor for XC-MTB performance. In addition, there is a relationship between MOP normalized to BM and body fat (BF), but not with fat-free mass (FFM) and body mass index (BMI) [38]. Therefore, the anthropometric profile of the cyclists seems to be a relevant factor for achieving success in competitions.…”
Section: Anthropometric Profilementioning
confidence: 99%
“…Interestingly, in 1997 [47], male and female professional cyclists had a BM with 6.2 and 5.4 kg more than in 2021 [5], respectively. In general, studies have reported that male cyclists have an average BF of 8.1 ± 3.5% (range: 5.1 to 15.6%) [3,29,38,40,41,43,[47][48][49]51], while female cyclists have an average BF of 13.2 ± 2.0% [47]. When verified according to performance level, the average BF reported in male cyclists was 10.5 ± 4.5% in trained cyclists [29,38,40], 7.3 ± 2.3% in well-trained [41,43] and 7.0 ± 3.2% in professionals [3,[47][48][49]51].…”
Section: Anthropometric Profilementioning
confidence: 99%
See 1 more Smart Citation